2018
DOI: 10.1039/c8ra03375g
|View full text |Cite
|
Sign up to set email alerts
|

Co-delivery of anti-PLK-1 siRNA and camptothecin by nanometric polydiacetylenic micelles results in a synergistic cell killing

Abstract: Recently, it has been shown that the efficiency of antitumoral drugs can be enhanced when combined with therapeutic siRNAs. In the present study, an original platform based on polydiacetylenic micelles containing a cationic head group able to efficiently deliver a small interfering RNA (siRNA) targeting the PLK-1 gene while offering a hydrophobic environment for encapsulation of lipophilic drugs such as camptothecin is developed. We demonstrate that the co-delivery of these two agents with our micellar system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…[26,27] Silencing of the expression of Plk1 by RNA interference with siPlk1 can be assessed directly by measuring the cell viability, as compared to delivery with control siRNA. [9] The transfection of siPlk1 in A459 cell line with the peptide amphiphiles leads to high levels of induced cell death, as compared to transfection with control siRNA at low siPlk1 concentration after 72 hours (20 nM siPlk1, N/P 8, see Figure 4 and S39). (Figure 5A and 5B; Figure S42).…”
Section: Silencing Of a Gene Of Therapeutic Interestmentioning
confidence: 96%
See 1 more Smart Citation
“…[26,27] Silencing of the expression of Plk1 by RNA interference with siPlk1 can be assessed directly by measuring the cell viability, as compared to delivery with control siRNA. [9] The transfection of siPlk1 in A459 cell line with the peptide amphiphiles leads to high levels of induced cell death, as compared to transfection with control siRNA at low siPlk1 concentration after 72 hours (20 nM siPlk1, N/P 8, see Figure 4 and S39). (Figure 5A and 5B; Figure S42).…”
Section: Silencing Of a Gene Of Therapeutic Interestmentioning
confidence: 96%
“…[6] PDA-micelles have been described as anticancer drug delivery agents, [7,8] and can be used for delivery of siRNA molecules. [9] With these PDA-micelles, we found that when the cationic headgroup was a histidine residue, we obtained vehicles that promote delivery of siRNA molecules into the cytoplasm of cells. [10] The good efficiency of the system is probably based on the fact that the imidazole group of His promotes release of the nucleic acid from the endosomal compartment through a proton sponge mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…One way to potentially improve the siRNA delivery of corrole conjugates is to explore modifying the corrole substituents with hydrophobic or cationic functional groups that may assist in the delivery of the siRNA to the cell. 2,22,26 In addition, to increase the cytotoxicity towards specific tissues, metalated corrole-siRNA conjugates can also be explored in the future. Previously, metalated corroles demonstrated increased cytotoxicity towards various cells based on the metal present in the corrole core.…”
Section: Organic and Biomolecular Chemistry Papermentioning
confidence: 99%
“…The current developments of PDT include the design of smart photosensitizers [13] among which supramolecular photosensitizers are emerging. [14] Only a few examples of studies combining PDT and gene delivery have been documented, using covalent siRNA vector-photosensitizer conjugates, [15] porous organo-silica nanoparticles, [16] dendrimers, [17] polydiacetylene micellar nanocarriers, [18] and polyelectrolytes. [19] In this work, we pursued a supramolecular approach to combine PDT with gene therapy using a simple cationic porphyrin as a dual photosensitizer and supramolecular siRNA vector.…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%